Ecological Impact of Large Herbivores at Artificial Waterpoints in Majete Wildlife Reserve, Malawi - Geenen, Kayla Adriana (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.